AC power analysis for second-order memory elements - Liu, Yue; Liu, Fang; Luo, Wanbo; Wu, Aoyun; Li, Hui (Frontiers in Physics, 2023)
As the product of a circuit’s voltage and current, apparent power (S) is of paramount necessary and importance in electric utilities, electronic, communication, and neural network systems. Based on the existing AC power analysis on the 2-terminal passive elements (i.e. R, L, and C), some in-depth researches on the AC apparent power calculations for the second-order memory elements and memristive systems are introduced to help with revealing their complex and unique nonlinear phenomena. This paper derives the forms of true power, reactive power, and apparent power for the proposed second-order memory elements (i.e. MR, MC, and ML) and reveals the difference between the ideal memory elements and the tradition passive ones (i.e. R, C, and L). For all involved memory elements, the harmonic values and an extra term occur in the expressions of powers to represent their memory characteristics. Especially, the true power is a function of a circuit's dissipative elements (usually resistances R), but not exactly the memristor (MR). Then, the corresponding curves could be depcited, which demonstrate the differences between R/C/L and MR/MC/ML and verified that the harmonic values existed in S_MR/S_MC/S_ML mean that it would perpetually supply energy when operated with alternating current.